2022
DOI: 10.1159/000519913
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High CDC6 Levels on Predicting Poor Prognosis in Colorectal Cancer

Abstract: <b><i>Introduction:</i></b> We investigated the function of cell division cycle 6 (CDC6) on the prognosis in colorectal carcinoma (CRC). <b><i>Methods:</i></b> CDC6 protein expression levels in 121 patients with colorectal cancer and adjacent normal mucosa were detected by immunohistochemistry. <b><i>Results:</i></b> Compared to adjacent normal tissues, CDC6 mRNA level was overexpressed in CRC tissues. Moreover, CDC6 protein levels were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…Furthermore, we detected expression level of five key genes in DNA replication pathway in SW480 after silencing NONHSAT136151. Previous studies demonstrated the protumor function in CRC of the five genes, CDK2, 36 , 37 CHK2, 38 , 39 CDC6, 40 , 41 CHK1 42 and CDC25A. 43 In our study, all five genes expression was reduced to some extent and four genes (CDK2, CDC6, CHK1 and CDC25A) showed the significantly decreased expression (Figure 6I,J ), which can partly explain that decreased NONHSAT136151 expression leads to the inhibition of CRC progression.…”
Section: Resultssupporting
confidence: 69%
“…Furthermore, we detected expression level of five key genes in DNA replication pathway in SW480 after silencing NONHSAT136151. Previous studies demonstrated the protumor function in CRC of the five genes, CDK2, 36 , 37 CHK2, 38 , 39 CDC6, 40 , 41 CHK1 42 and CDC25A. 43 In our study, all five genes expression was reduced to some extent and four genes (CDK2, CDC6, CHK1 and CDC25A) showed the significantly decreased expression (Figure 6I,J ), which can partly explain that decreased NONHSAT136151 expression leads to the inhibition of CRC progression.…”
Section: Resultssupporting
confidence: 69%
“…In further agreement with overexpression of DNA replication-licensing factors in human PDAC, deregulation of replication licensing has been shown to cause replication stress, DNA damage and genomic instability, contributing to malignant transformation (41)(42)(43). In this context, we previously showed CDT1 to be overexpressed in colorectal cancer (21,44) and hepatocellular carcinoma (45), and several reports support the tumor-promoting roles of CDT1, CDC6 and MCM7 in other cancer types (45)(46)(47)(48)(49)(50). Interestingly, CDC6 disruption in pancreatic cancer cells leads to chromosomal instability and it is potentially linked to the KRAS signaling pathway (47,51,52).…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, CHEK1 responds to DNA damage in CRC cells and TP53 status influences its function ( Gali-Muhtasib et al, 2008 ). CDC6 is overexpressed in CRC tissues and has been correlated with metastasis and prognosis ( Yang et al, 2022 ). Thus, CDC6 may serve as a valuable biomarker and a potential therapeutic target for CRC.…”
Section: Discussionmentioning
confidence: 99%